1054 Early Kangaroo Mother care for unstable neonates <2000g in a resource-limited Gambian hospital: intervention duration and implementation realities. (17th August 2022) - Walker, Georgia; Gai, Abdou; Kebbeh, Bunja; Njie, Yusupha; Samateh, Ahmadou Lamin; Roca, Anna; Lawn, Joy; Brotherton, Helen
Abstract : Aims: New evidence indicates that Kangaroo Mother Care (KMC) commenced immediately after delivery reduces mortality among neonates weighing 1-1.8kg. 1 In order to support the widespread implementation of KMC for these neonates it is essential to understand the delivery of KMC to unstable neonates in pragmatic low-resource hospital settings and identify any factors associated with prolonged duration. Aim and objectives: This study aimed to understand the delivery of KMC to unstable neonates weighing <2000g in a pragmatic research setting in The Gambia. The objectives were to understand: 1. The regimen of KMC delivered, including daily duration and reasons for interruption to skin-to-skin contact 2. Factors predicting the daily duration of KMC delivered to unstable neonates Methods: This study was a secondary analysis of data from the eKMC randomised controlled trial, conducted at the only teaching hospital and level 2+ neonatal unit in The Gambia between March 2018 – May 2020. Early KMC (onset within 24h of admission) was compared to standard care for mild-moderately unstable neonates weighing <2kg and receiving oxygen, parenteral fluids and antibiotics. 2 A descriptive analysis of the directly-observed skin-to-skin sessions delivered to all neonates who were randomised to the intervention group and who received early KMC prior to stabilisation was completed. Univariate and multivariate regression were conducted to identify predictors of daily duration. Results: 136 neonates were eligible for inclusion, and 5797 sessions (comprising 12 292 hours of skin-to-skin contact) were analysed ( table 1 ). The median daily duration was 6.7 hours (IQR 4.3-8.5) via a regimen of 3 (IQR 2.6–4.2) sessions per day, with each session lasting 2h 20mins (IQR 2h-2h 40mins), for a total of 10 (IQR 5.3–16.0) days. In the immediate postpartum period when many mothers were unavailable to attend the neonatal unit, non-maternal female caregivers provided half of all first KMC sessions. 70% of sessions were interrupted in order for the caregiver to feed the baby ( figure 1 ). Twins received almost 40% less skin-to-skin contact than singletons. No predictors of KMC duration were identified. Conclusion: Providing early KMC prior to stabilisation is feasible in low-resource pragmatic settings, however achieving prolonged durations >10 hours/day is challenging, with the main barriers being the early postpartum absence of mother, delivery to twins, and feeding logistics. Two major pathways to enhancing delivery of KMC to this population are 1.) assisting mothers to feed their neonates without disrupting the skin-to-skin position, and 2.) identifying and minimising barriers to delivering KMC to twins. Involving and empowering the extended family in the care of the unstable neonate, especially potential surrogate caregivers, is also of crucial importance. References: Immediate 'Kangaroo Mother Care' and Survival of Infants with Low Birth Weight. N Engl J Med [Internet]. 2021 May 27 [cited 2022 Feb 12];384(21):2028–38. Available from: https://www.nejm.org/doi/full/10.1056/NEJMoa2026486 Brotherton H, Gai A, Kebbeh B, Njie Y, Walker G, Muhammad AK, et al. Impact of early kangaroo mother care versus standard care on survival of mild-moderately unstable neonates <2000 grams: A randomised controlled trial. EClinicalMedicine. 2021 Sep 1;39:101050.